Analisis Efektivitas UU No 22 Tahun 2001 terhadap Praktik Jualan Bensin Eceran Masyarakat Kota Timur Gorontalo - Arifah, Nur Afifah Masuara; Putra, Abdur Rahman Adi Saputera (Madani: Jurnal Pengabdian Ilmiah, 2020)
This study aims to examine the effectiveness of Law No. 22 of 2001 on the practice of retail gasoline selling by the people of Kota Timur Gorontalo, and uses a type of field research that focuses on the results of data collection from predetermined informants. The research method used is descriptive qualitative, namely research that is intended to gather information from people and observed behavior. The data sources used are primary and secondary data sources, then the data that has been collected will be analyzed using descriptive analysis methods. The results showed that the implementation of Law No. 22 of 2001 in the practice of selling retail gasoline by the community in Kota Timur Gorontalo has not been effective. It is proven that during 2020, the number of petrol depots in the area has increased to 98 petrol depots which also have not obtained a commercial business license. The factors that cause the ineffectiveness of the application of the law are the legal instruments, law enforcement officers, the factors of the community members who are affected by the scope of legal regulations and cultural factors. Therefore, the government's socialization efforts are needed in the form of counseling about the consequences, sanctions of criminal acts and providing information to administer the licensing of retail gasoline sales